2019
DOI: 10.1101/709873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maintenance of adaptive dynamics and no detectable load in a range-edge out-crossing plant population

Abstract: During range expansion, edge populations are expected to face increased genetic drift, which in turn can alter and potentially compromise adaptive dynamics, preventing the removal of deleterious mutations and slowing down adaptation. In plants, range expansion is often concomitant with a shift in mating system. In the Northern American subspecies Arabidopsis lyrata ssp lyrata, range expansion has been associated with the evolution of a mixed mating system and the accumulation of a burden of deleterious mutatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 142 publications
(213 reference statements)
0
11
0
Order By: Relevance
“…Similarly, an experimental study in brook trout ( Salvelinus fontinalis ) suggests that low genetic diversity does not prevent or predict transplantation success into fishless ponds over a wide gradient of ecological variables ( 56 ). As another example, dramatically bottlenecked northern European populations of Arabidopsis lyrata and Arabidopsis thaliana show strong genomic footprints of adaptation ( 57 , 58 ), and experimental evidence suggests that their strongly reduced genetic diversity has not affected their ability to adapt to local environmental conditions ( 59 61 ). To investigate the determinants of the rate of genetic adaptation more generally, population genomic studies have analyzed genome-wide polymorphism and divergence data from many different species and concluded that low-diversity taxa do not seem to accumulate adaptive substitutions at a substantially lower rate than high-diversity taxa ( 62 , 63 ), although within certain groups such a relationship might exist ( 63 , 64 ).…”
Section: Neutral Diversity Does Not Predict Adaptive Potentialmentioning
confidence: 99%
“…Similarly, an experimental study in brook trout ( Salvelinus fontinalis ) suggests that low genetic diversity does not prevent or predict transplantation success into fishless ponds over a wide gradient of ecological variables ( 56 ). As another example, dramatically bottlenecked northern European populations of Arabidopsis lyrata and Arabidopsis thaliana show strong genomic footprints of adaptation ( 57 , 58 ), and experimental evidence suggests that their strongly reduced genetic diversity has not affected their ability to adapt to local environmental conditions ( 59 61 ). To investigate the determinants of the rate of genetic adaptation more generally, population genomic studies have analyzed genome-wide polymorphism and divergence data from many different species and concluded that low-diversity taxa do not seem to accumulate adaptive substitutions at a substantially lower rate than high-diversity taxa ( 62 , 63 ), although within certain groups such a relationship might exist ( 63 , 64 ).…”
Section: Neutral Diversity Does Not Predict Adaptive Potentialmentioning
confidence: 99%
“…In areas located at the edge of the distribution range of A. thaliana, populations may have accumulated an excess of deleterious mutations in the aftermath of their genetic isolation [39,88]. This could have resulted in a mutational load that would have decreased fitness components such as plant growth, because it influences the resources available for the production of progeny [1,20,22]. We thus hypothesized that the lower FS observed in Northern Europe may result from maladaptive forces associated with the demographic history of the region.…”
Section: No Association Between Per-individual Burden and Growthmentioning
confidence: 99%
“…Genetic variation in growth rate may also arise in the absence of a compelling environmental change, as a consequence of population genetics processes. In bottlenecked populations, or in the aftermath of rapid range expansion, increased drift hampers the efficient removal of deleterious mutations, and individuals may become less fit [18][19][20][21][22]. Because plant growth is a component of fitness, genotypes carrying a larger burden of deleterious mutations may show decreased growth.…”
Section: Introductionmentioning
confidence: 99%
“…S9H-J). To gain further insight into the evolutionary forces operating on these genes in A. lyrata, we examined nucleotide polymorphism within a local A. lyrata population [44][45][46] . The average number of pairwise differences did not differ significantly across groups of genes, and was similar to that of the control genes (Fig.…”
Section: Genes With Magnified Plastic Responses In a Lyrata Evolve Under Increased Evolutionary Constraintsmentioning
confidence: 99%
“…To confirm that the amino-acid sequence of genes with a magnified plasticity are subject to stronger evolutionary constraints, we estimated the distribution of fitness effects (DFE) of new non synonymous mutations for each gene group, using the software fitδaδi 47,48 . Parameters of a demographic model for the A. lyrata population have been previously determined 46 .…”
Section: Genes With Magnified Plastic Responses In a Lyrata Evolve Under Increased Evolutionary Constraintsmentioning
confidence: 99%